2012
DOI: 10.1292/jvms.12-0109
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Aspirin with Trehalose May Decrease the Incidence of Gastric Injuries in Healthy Dogs

Abstract: ABSTRACT. Trehalose has several novel anti-inflammatory and cell-protective functions. We hypothesized that lyophilized aspirin/trehalose could decrease the severity of aspirin-induced gastropathy. Thirteen dogs were assigned into aspirin, lyophilized aspirin/trehalose, and control groups, and the gastric lesions were assessed on gastroscopy with the modified Lanza scale. Another 6 dogs were used to measure the plasma aspirin concentration by high-performance liquid chromatography after aspirin or lyophilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
2
2
0
Order By: Relevance
“…We speculate that skin penetration of NSAIDs is not inhibited by co-lyophilization with trehalose. These considerations are in agreement with those from our previous study, which showed that co-lyophilization with trehalose does not alter the absorption of aspirin [10]. …”
supporting
confidence: 93%
See 3 more Smart Citations
“…We speculate that skin penetration of NSAIDs is not inhibited by co-lyophilization with trehalose. These considerations are in agreement with those from our previous study, which showed that co-lyophilization with trehalose does not alter the absorption of aspirin [10]. …”
supporting
confidence: 93%
“…This is consistent with our recent study that co-lyophilized aspirin/trehalose decreased the severity of aspirin-induced gastric ulceration in healthy dogs [10]. We hypothesize that co-lyophilization accelerates the specific interaction between the NSAIDs and trehalose and that this interaction is necessary for a marked reduction of NSAID-induced cell damage.…”
supporting
confidence: 93%
See 2 more Smart Citations